The relationship between input and literacy and metalinguistic development: A study with Chinese–English bilinguals. (February 2020) - Kuo, Li-Jen; Ku, Yu-Min; Chen, Zhuo; Gezer, Melike Ünal
The purpose of this study was to examine the relationship between input and literacy/ metalinguistic development in bilingual children. Participants included fourth-grade Chinese-English bilinguals from Taiwan and the USA. The two groups were comparable in socioeconomic status, non-verbal IQ, and the amount of literacy instruction in Chinese and English, but the bilingual participants from Taiwan had more exposure to Chinese and less exposure to English outside of school than their US counterparts. A battery of standardized and researcher-developed measures of literacy and metalinguistic skills were administered in English and Chinese. Results showed that, in general, the greater the amount of input, the more superior the linguistic/metalinguistic development. However, advantages associated with input appeared to be offset by a more balanced bilingual experience on measures that assessed higher levels of metalinguistic awareness. In addition, hierarchical regression analyses showed that morpho-syntactic awareness made a unique contribution to reading comprehension beyond that by vocabulary and morphological awareness only among the participants in Taiwan. The findings make several noteworthy contributions to research on input among bilingual learners. Firstly, the present study highlights the importance of recognizing the variations of bilinguals who speak the same pair of languages, and the impact of linguistic input outside of the school context on language and literacy development in academic settings. Secondly, findings from the present study call for a broader conceptualization of the relationship between input and linguistic/metalinguistic development, and underscore the importance of examining how input may impact the relationship of linguistic and metalinguistic variables. Finally, the present study highlights the need to re-conceptualize input. Indicators of input should go beyond to the quantity or quality of exposure to the assessed language, and be expanded to include the degree of balance in both languages.